Study of social network interference of memory processes in adolescence - V. E. Baryshnikova; V. B. Nikishina; E. A. Petrash; V. A. Sotnikov; E. I. Kulikova (Цифровая социология)
Memory is the fundamental basis of human learning. Conceptual assessment and study of the memory mechanisms, its formation, consolidation and preservation at different levels of the structural and functional organization of the nervous system constitutes the necessary knowledge for solving many problems of practical and fundamental psychology. This article presents the study of memory, namely the process of its transition from a short-term to a more stable long-term form in a digital environment under the influence of the interference factor of social networks. The aim of the work is to study the influence of the social network interference factor on the processes of consolidation and reconsolidation of memory in adolescence. The total sample size was 68 adolescents aged 12–17 years. The authors conducted an experiment to achieve this goal. Its results showed that adolescents have difficulty remembering information in the form of short, successive videos in the digital space. It was found that videos that are characterized not only by visual accompaniment, but also by speech production are subject to better memorization. Under the influence of the interfering factor of social networks, adolescents faced difficulties in linking individual elements of stimuli with each other – they connected elements of one video with elements of another. According to one of the provisions of the theory of interference, information storage is characterized by the “unbinding” of representations of objects, followed by their reverse linking in an arbitrary combination during further reproduction.